2016
DOI: 10.1097/qai.000000000001107
|View full text |Cite
|
Sign up to set email alerts
|

Linkage to Primary Care and Survival After Hospital Discharge for HIV-Infected Adults in Tanzania: A Prospective Cohort Study

Abstract: Introduction Little is known about outcomes after hospitalization for HIV-infected adults in sub-Saharan Africa. We determined 12-month, post-hospital mortality rates in HIV-infected vs. uninfected adults and predictors of mortality. Methods In this prospective cohort study, we enrolled adults admitted to the medical wards of a public hospital in northwestern Tanzania. We conducted standardized questionnaires, physical examinations, and basic laboratory analyses including HIV testing. Participants or proxies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Regardless, the combination of high repeat inpatient utilization and failure to successfully follow-up with outpatient care emphasizes the need to develop patient-centered approaches to post-hospital health management [26,27]. While a modest number of deaths and readmissions were captured and the data were largely consistent with previous reports [2831], we hypothesize that mortality and readmission rates were higher, especially given the large number of participants that were unreachable. The study was limited in that it consisted of a convenience sample, recruited from a single center in the North West province of South Africa.…”
Section: Discussionsupporting
confidence: 64%
“…Regardless, the combination of high repeat inpatient utilization and failure to successfully follow-up with outpatient care emphasizes the need to develop patient-centered approaches to post-hospital health management [26,27]. While a modest number of deaths and readmissions were captured and the data were largely consistent with previous reports [2831], we hypothesize that mortality and readmission rates were higher, especially given the large number of participants that were unreachable. The study was limited in that it consisted of a convenience sample, recruited from a single center in the North West province of South Africa.…”
Section: Discussionsupporting
confidence: 64%
“…These findings highlight a population with HIV at particularly high risk of death and add new insight to similar high post-hospital mortality from similar single hospital studies. Studies from South Africa, Tanzania, and Kenya have reported 6 to 12 month mortality ranging between 18 and 50% [5, 9–11, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Reported inpatient mortality for people with HIV in sub-Saharan Africa ranges from 15–45% [68], a level of mortality that may persist following hospital discharge. For example, a study from Tanzania reported 50% mortality one year from hospital discharge [9] and studies from South Africa have reported 18–31% mortality six months from discharge [10, 11]. A better understanding of outcomes, and factors associated with poor outcomes may help to identify opportunities to reduce HIV-associated mortality.…”
Section: Introductionmentioning
confidence: 99%
“…For example, individuals with nonsuppression of HIV RNA could be identified and further evaluated for virological failure and suboptimal retention [7]. Hospitalization also often precedes death, not just during admission [8] but also during the postdischarge period [9, 10]. Mortality during the 6 months after a hospitalization was 23.2% in Uganda [10] and 42.9% in Tanzania [9], and HIV-infected individuals had 1.54 times the odds of postdischarge mortality compared with uninfected individuals [9].…”
mentioning
confidence: 99%